2017
DOI: 10.1002/ece3.3218
|View full text |Cite
|
Sign up to set email alerts
|

How relative size and abundance structures the relationship between size and individual growth in an ontogenetically piscivorous fish

Abstract: While individual growth ultimately reflects the quality and quantity of food resources, intra and interspecific interactions for these resources, as well as individual size, may have dramatic impacts on growth opportunity. Out‐migrating anadromous salmonids make rapid transitions between habitat types resulting in large pulses of individuals into a given location over a short period, which may have significant impact on demand for local resources. We evaluated the spatial and temporal variation in IGF‐1 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…; Chamberlin et al. ), were scarcely observed in the Nisqually diet samples except for in the offshore area in May. Consequently, this was the only month during which modeled GRP in the offshore habitat reached values that were equivalent to that in the tidal marshes, regardless of P cmax .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…; Chamberlin et al. ), were scarcely observed in the Nisqually diet samples except for in the offshore area in May. Consequently, this was the only month during which modeled GRP in the offshore habitat reached values that were equivalent to that in the tidal marshes, regardless of P cmax .…”
Section: Discussionmentioning
confidence: 87%
“…Although plankton and aquatic macroinvertebrates can be highly abundant in nearshore and offshore areas, piscivory is believed to bolster salmonid growth by providing a large, high-energy alternative to smaller crustaceans such as amphipods and crab larvae (Brodeur 1991;Daly et al 2009;Litz et al 2017). Forage fish, which are a major source of prey for some Puget Sound Chinook Salmon as they move to the offshore (Duffy et al 2010;Chamberlin et al 2017), were scarcely observed in the Nisqually diet samples except for in the offshore area in May. Consequently, this was the only month during which modeled GRP in the offshore habitat reached values that were equivalent to that in the tidal marshes, regardless of P cmax .…”
Section: Formentioning
confidence: 99%
“…A more thorough analysis relating Puget Sound juvenile salmon diets to the historic seasonal prevalence of forage fish and fish larvae would be needed to determine the relationship between piscivory and prey availability. Such an analysis would represent a pivotal scientific contribution to the salmonid literature, as there is currently little historic data to draw upon in the Pacific Northwest (but see Chamberlin et al ).…”
Section: Discussionmentioning
confidence: 99%
“…(Brodeur 1991), but digested fish were detected in only 2 of our 244 stomach samples. We suspect that the lack of piscivory is indicative of reduced availability of fish larvae and small forage fish in the Nisqually River delta, since juvenile Chinook Salmon as small as 75 mm have been known to consume other fish (Daly et al 2009; Chamberlin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These potential interactions will likely vary regionally and/or locally, as suggested by previous studies of juvenile Chinook in the Salish Sea (Chamberlin et al 2017). These potential interactions will likely vary regionally and/or locally, as suggested by previous studies of juvenile Chinook in the Salish Sea (Chamberlin et al 2017).…”
Section: Discussionmentioning
confidence: 75%